A ratiometric two-photon probe for quantitative imaging of mitochondrial pH values - Sarkar, Avik Ranjan (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Mitochondrial pH (pH(mito)) is known to be alkaline (near 8.0) and has emerged as a potential factor for mitochondrial function and disorder. We have developed a ratiometric two-photon probe (CMP1) for quantitative analysis of pH(mito) in live cells and tissues. This probe is designed to function by controlling the intramolecular charge transfer from 2-naphthol, having an ideal pK(a) value (7.86 ± 0.05) in the cells to monitor pH(mito). This transition results in a marked yellow to red emission color change in response to pH alterations from 6.0 to 9.0. CMP1 exhibits easy loading, selective and robust staining ability of mitochondria, low cytotoxicity, and bright two-photon excited fluorescence in situ, thereby allowing quantitative imaging of the pH(mito) in live cells and tissues. The ratiometric TPM imaging clearly reveals that subcellular distribution of the pH(mito) values is heterogeneous, with the pH(mito) values in the perinuclear region being higher than those at the periphery of the cells. The changes of pH(mito) values on carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment and autophagic processes were also investigated along with their morphological alterations at specific subcellular positions. We also used CMP1 to visualize the pH(mito) values of Parkinson's disease model astrocytes as well as living hippocampal tissues. Our results demonstrate that CMP1 will be useful as a quantitative imaging probe to study pH(mito) in biomedical research.